Diversity and abundance of selected animal species in undisturbed forest, selectively logged forest and plantations in East Kalimantan, Indonesia - Wilson, Wendell L.; Johns, Andrew D. (Elsevier, 1982)
Animal surveys were conducted in six habitat types within the timber concession of PT International Timber Corporation Indonesia, East Kalimantan. Species diversity was found to be similar in undisturbed forest and in 3- to 5-year-old selectively logged forest, although densities in the latter were considerably less. Both diversity and density declined drastically in forestry plantations, but certain of the species remaining caused significant damage to young trees. Although few animals were observed in areas where there was active road construction and timber felling, their densities in adjacent undisturbed forest areas did not increase, suggesting that the level of local migration actually is low. It is suggested that recolonisation of old logged forest can occur successfully provide that the level of hunting is low and that adjacent areas of undisturbed forest remain to provide a population pool from which colonists can spread.